Cesium/Xenon dual beam sputtering in a Cameca instrument. (22nd September 2014) - Pureti, R.; Douhard, B.; Joris, D.; Merkulov, A.; Vandervorst, W.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; et al.
<x xml:space="preserve">Abstract</x> Although the use of cesium (or oxygen) primary ions in secondary ion mass spectrometry (SIMS) enabled its success in microelectronics, issues arise at ultra‐low energies, as required for extreme depth resolution, as the sputter yield becomes very small such that one enters the regime of ion beam deposition instead of material erosion. A potential solution is then to lower the Cs supply by using a Cs/Xe co‐sputtering as introduced by ION‐TOF and explored extensively by J. Brison. In this work, we describe a somewhat similar implementation in a Cameca SC Ultra and assess its performance and impact on ion yields. Because of the specific Cameca instrumental configuration, one alternates with short time intervals between Cs+ and Xe+ primary ions in the same ion column. Depending on the time intervals used, this approach leads to either quasi‐simultaneous sputtering (intervals ~80 ms) or sequential (intervals >1 s) sputtering. An exponential variation of the Si− yield is observed when the Cs beam fraction varies from 0 (Xe) to 1 (Cs) and is ascribed to the corresponding increase in the near surface Cs concentration, CCs. Moreover, we observed detailed timing effects of the beams implying that the same nominal CCs may lead to different secondary ion yields suggesting effectively a different CCs. These effects are further investigated by observing the finer details of Cs accumulation and migration mechanisms in situ. Finally, when analysing SiGe/Si layers, it is found that with increasing Cs/Xe ratio, the decay lengths tend to decrease whereas matrix effects at interfaces show an opposite trend. Copyright © 2014 John Wiley & Sons, Ltd.